P16INK4A EXPRESSION AS A POTENTIAL PROGNOSTIC MARKER IN CERVICAL PRECANCEROUS AND CANCEROUS LESIONS IN MOROCCO - Yassine Zouheir; Taoufiq Fechtali; Nadia Elgnaoui (European Scientific Journal, ESJ, 2015)
Introduction :The overexpression of p16INK4a is considered to be strong and consistent in HPV-induced cancers. The objective of this study was to investigate the presence of HPV DNA in cervical biopsies, and to study the overexpression of p16INK4a as a marker of precancerous and cancerous lesions of the cervix. Material and methods :A total of 75 cervical biopsies were included in this study involving cervicitis (n = 11), mild dysplasia (n = 17), severe dysplasia (n = 30) and invasive carcinomas (n = 17). The presence of HPV was assessed using an examination in situ hybridization (CSA). p16INK4a protein expression was investigated by immunohistochemistry. Results: p16INK4a expression was very low in benign cervical lesions, while 18.8% of these lesions showed positivity for HPV DNA detection. Forty seven percent of mild dysplastic lesions presented overexpression of p16INK4a protein, and 76.4% were HPV positive. Strong signal of p16INK4a was observed in 100% of severe dysplastic lesions, and in 94.2% of invasive carcinoma. HPV DNA was detected in 83.3% of severe dysplastic lesions, and in 82.3% of invasive carcinoma. Conclusion: This pattern of overexpression demonstrates the potential use of p16INK4a as a diagnostic marker to recognize evolution of precancerous disease in the cervix.